Agronomic diversity of several soybean putative mutant lines resulting from gamma-rays irradiation in M6 generation - NILAHAYATI, NILAHAYATI; NAZIMAH, NAZIMAH; HANDAYANI, RD. SELVY; SYAHPUTRA, JAKA; RIZKY, MUHAMMAD (Nusantara Bioscience, 2022)
Abstract. Nilahayati, Nazimah, Handayani RDS, Syahputra J, Rizky M. 2022. Agronomic diversity of several soybean putative mutant lines resulting from gamma-ray irradiation in M6 generation. Nusantara Bioscience 14: 34-39. Soybean is one of the foremost commodities for Indonesian people. Therefore, increasing domestic production must continue to be pursued absolutely. One way to do this is to use the assembly technology of new superior varieties with better and adaptive properties. This study aims to determine the agronomic diversity and yield of soybean putative mutant lines resulting from gamma irradiation in M6 ??generation. The research was conducted in Paloh Lada Village, Dewantara Subdistrict, Aceh Utara District, Indonesia, from July 2021 to October 2021. The tested genotypes consisted of 8: Kipas Putih variety (parent variety), Anjasmoro variety (comparison variety), M.1.1.3, M.5.2.1, M.5.2.3, M.1.1.8, M.1.1.9, and M.1.1.17 mutant lines. The results showed that the agronomic diversity of the tested mutants differed from the parents and comparison variety. In addition, we obtained early maturity and high yielding mutant in the M7 ??generation. The mutant line with a high yield and equivalent to its parents was M.1.1.8, with a production of 4.37 tons.ha-1. Mutant lines with early maturity were M.1.1.9, M.5.2.1, and M.1.1.3 lines with a harvesting age of 83 days after planting (DAP).